Measuring the Influence of Environmental Policy on Economic Development of the Countries: EU-28 Scope - Vovk, Marta; Вовк, Марта; Varenyk, Viktoriia; Вареник, Вікторія; Pestovska, Zoia; Пестовська, Зоя; Atamas, Petro; Атамас, Петро; Atamas, Oleksandr; Атамас, Олександр Петрович; Shevchenko, Valentyna; Шевченко, Валентина (Ekonomický ústav SAV, v. v. i., 2021)
In current paper, we have researched the influence of environmental policy stringency (EPS) on economic development of the EU-28. The problem of identifying the influence of stringency of environmental policy (EP) on economic development of the EU-28 is that currently there is no well-established understanding of what economic results can be achieved depending on the extent of EPS within a separate country. The paper aims at making contribution to theoretical, empirical and political scopes of perception of EP as an independent factor of economic development of the EU-28. The results of research indicate that EPS is significant factor of economic development of the EU countries. У цій статті ми досліджували вплив екологічної політики суворість (EPS) щодо економічного розвитку ЄС-28. Проблема виявлення впливу жорсткості екологічної політики (EP) на економічний розвиток ЄС-28 полягає в тому, що на даний момент немає чітко усталеного розуміння того, яких економічних результатів можна досягти залежно від масштабів EPS. Стаття має на меті зробити внесок у теоретичні, емпірико-політичні рамки сприйняття ЕП як самостійного чинника економічний розвиток ЄС-28. Результати досліджень свідчать, що EPS є вагомим фактором економічного розвитку країн ЄС.
Вимірювання впливу екологічної політики на економічний розвиток країн: сфера дії ЄС-28
Keywords: environmental policy stringency; суворість екологічної політики; environmental policy; екологічна політика; export; експорт